PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI BEBAS SISWA KELAS V SD NEGERI 30 KECAMATAN PINGGIR KABUPATEN BENGKALIS - Indah, Titik Rosita; Erlisnawati, Erlisnawati; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the ability to write poetry fifth graderes SDN 30 Pinggir still low with an average value of 55,84 and minimum completenness criteria (KKM) is 70. Between students, amounting to 20 people only 2 students who achieve classical KKM with 10%. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation of Contextual Teaching and Learning (CTL)can improve ability to write poetry at SDN 30 Pinggir. The research was conducted on mai 31, 2015 to april 9, 2015by 2 cyclees. Subjects were students of SDN 30Pinggir, totalling 20 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and ability to write poetry. Based on the conduct of research with the implementation of learning models obtained results Contextual Teaching and Learning (CTL) of activity the teacher in the lerning process in cycle I frist meeting was 75% and at the second meeting of teacher activity increased by 6,3% to 81,3%. cycle II firs meeting and the second meeting of activity increased by 6,2% to 87,5% and the second meeting of activity increased by 6,2% to 93,7%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 62,5% and at second meeting of activity increased 12,5% to 75%% and a second meeting of activity increased 6,2% improve to 81,2%. At the firs meeting of the second meeting of activity increased 12,5% to93,7%%.This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 55,84. In the first cycle improve an average of 68,76 with increase as 23,13% and an impove in the second with an average of 72,09 with increase as 29,10%. Result in the research that the implementation of Contextual Teaching and Learning (CTL) can improve ability to write poetry at fifth SDN30 Kecamatan Pinggir Kabupaten Bengkalis.Key Words :Contextual Teaching and Learning (CTL),Ability To Write Poetry